Extremely low-frequency magnetic fields significantly enhance the cytotoxicity of methotrexate and can reduce migration of cancer cell lines via transiently induced plasma membrane damage. - Stratton, Dan; Malibha-Pinchbeck, Memory; Inal, Jameel (Academic Press, Elsevier, 2022)
Extra Low-frequency Magnetic Fields (ELF-MFs) significantly enhance cellular uptake of methotrexate by inducing transient plasma membrane pores/damage. This enhanced 'dose loading' of methotrexate via the electromagnetically induced membrane pores leads to similar outcomes as the normal control while using significantly smaller therapeutic doses in vitro when compared to non-ELF-MF treated control. Approximately 10% of the typical therapeutic dose yielded similar results when used with ELF-MF. ELF-MFs increase PC12, THP-1 and HeLa proliferation in vitro (120% of the control). Analysis of adherent cells demonstrate significantly less migration towards an induced scratch injury (20 μm in 24 h when compared to a control). Our results suggest an important role for the use of ELF-MFs in the treatment of tumours that opens some new and exciting possibilities including using smaller therapeutic doses of chemotherapeutic agents and disrupting tumour metastasis.